la lectura como estrategia metodológica para potenciar la lecto-escritura en niños y niñas de cuarto año de educación general básica de la unidad educativa fiscomisional San Juan Bautista de la parroquia San José, cantón Catamayo, provincia de Loja, periodo lectivo 2014-2015 - Torres Armijos, Vanessa Maribel (2016)
This thesis titled READING AS METHODOLOGICAL STRATEGY TO PROMOTE LITERACY IN CHILDREN OF FOURTH YEAR OF BASIC GENERAL EDUCATION OF EDUCATIONAL UNIT Fiscomisional "SAN JUAN BAUTISTA" PARISH SAN JOSE, CANTON CATAMAYO, Loja province, PERIOD LECTIVO 2014-2015, had as general objective to determine the extent to which teachers apply reading as methodological strategy to promote literacy; research is cross and pre-experimental type, in which the following methods were used: comprehensive, scientific, descriptive, analytical, synthetic and workshop; the techniques used were based on direct observation and application of survey; instruments used were the observation guide and questionnaire. For data analysis and interpretation of statistical tables and graphic representation it was used. After processing the information it was established as a conclusion that teacher does not use reading as a strategy to promote literacy, a reality that is reflected in the results of the diagnosis, since it was found that most students do not understand properly readings; for this research they involved seventeen students and one teacher is why the teacher is recommended readings as a strategy to encourage students literacy and achieve meaningful learning them.